2018
DOI: 10.3390/toxins10120530
|View full text |Cite
|
Sign up to set email alerts
|

Chestnut Drying Is Critical in Determining Aspergillus flavus Growth and Aflatoxin Contamination

Abstract: Chestnut drying is used to prevent postharvest losses and microorganism contamination during storage. Several studies reported the contamination by aflatoxins (AFs) produced by Aspergillus spp. in chestnuts. The effect of drying temperatures (from 30 to 50 °C) was evaluated on the growth of A. flavus and the production of aflatoxins in chestnuts. The influence of the treatment on the proximate composition, the total phenol content and antioxidant activity of chestnuts was considered. Fungal colonization was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 48 publications
0
9
0
2
Order By: Relevance
“…A. flavus has an outstandingly high heat tolerance in comparison to other fungi with an upper tolerance limit of 40 • C (Neme and Mohammed, 2017). Prencipe et al (2018) also found that while the growth of A. flavus was suboptimal above 40 • C this relatively high temperature resulted in the most intensive aflatoxin synthesis on chestnut. Hawkins et al (2005) found that 60 • C drying temperature still had no adverse effect on A. flavus thriving on corn kernels but raising the temperature up to 70 • C significantly decreased fungal infection.…”
Section: Fungal Activity and Aflatoxin Production In Stored Grainsmentioning
confidence: 94%
“…A. flavus has an outstandingly high heat tolerance in comparison to other fungi with an upper tolerance limit of 40 • C (Neme and Mohammed, 2017). Prencipe et al (2018) also found that while the growth of A. flavus was suboptimal above 40 • C this relatively high temperature resulted in the most intensive aflatoxin synthesis on chestnut. Hawkins et al (2005) found that 60 • C drying temperature still had no adverse effect on A. flavus thriving on corn kernels but raising the temperature up to 70 • C significantly decreased fungal infection.…”
Section: Fungal Activity and Aflatoxin Production In Stored Grainsmentioning
confidence: 94%
“…(49) and Turan and Islam (48) suggest to dry hazelnuts with higher temperature (43-49 °C and 45 °C, respectively). For other nuts, the best drying temperatures were found to be above 40 °C: 42 °C for peanuts (18) and 45 °C for chestnuts (36). In this work, hazelnuts were artificially inoculated, while fungal growth and aflatoxin production were promoted by adjusting the moisture content, as a result, high level of aflatoxins were produced especially between 30 °C and 40 °C.…”
Section: Discussionmentioning
confidence: 89%
“…Mycotoxin production is often promoted under suboptimal growth conditions as an adaptive response (36,39,40). For example, in chestnuts, drying at 40 °C resulted in a significant reduction of fungal growth but also in a higher production of aflatoxins (36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the fatty acids of hazelnut oil, palmitic acid (2.96-7.40%) is the main saturated fatty acid (SFA). The highest share of fatty acids is monounsaturated fatty acids (MUFAs), as oleic acid (73.1%-90.7%), and polyunsaturated fatty acids (PUFAs) as linoleic acid (4.4-16%) [41,42]. Due to the uniqueness of the matrices, the composition of the solvent applied for extraction is a crucial parameter during the development of a multi-mycotoxin method.…”
Section: Resultsmentioning
confidence: 99%